Silica gel chromatographic study of phenolic compounds in some cultivated cucurbits - Baitha, Suresh N; Pandey, Vijoy S (Himalayan Journal of Sciences, 2006)
Phenolic compounds in the leaves of cultivated cucurbits viz. Trichosanthes dioica Roxb., Lagenaria siceraria (Molina) Standl., Luffa cylindrica (L.) Roem., and Luffa acutangula (L.) Roxb. were carried out through silica gel chromatographic separation to ascertain their relative phylogenetic position. On phytochemical analysis, paired affinity, group affinity and isolation value supported the inclusion of these species in the same tribe Cucurbiteae on the basis of earlier cytotaxonomic studies. The two species of Luffa showed the closest phytochemical affinity and occupied as intermediate position between Lagenaria and Trichosanthes. Luffa was distantly related to other two genera having paired affinity values of less than 50%.Key words: Silica gel chromatography, separation of phenolic compounds, cultivated cucurbitsHimalayan Journal of Sciences 1(2): 123-125, 2003